Teknologi Sebagai Alat Koreksi Miskonsepsi dalam Pembelajaran IPA Materi Sel : A Systematic Literature Review (SLR) - Fauziah, Sadah; Irwansyah, Ferli Septi; Agustina, Tri Wahyu; Supriyatna, Ateng (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2024)
This research is a systematic literature review which aims to explore the implementation of technology in learning cell material in an effort to prevent and reduce misconceptions. Misconceptions in cell material were identified with a percentage of 20.04% understanding the concept, 48.81% having misconceptions and 31.15% not understanding the concept. The application of technology in cellular learning has paved the way for educators such as teachers to help students learn abstract or complex science material. The integration of technology into cellular learning allows students to reduce misconceptions. The method used in this research is Systematic Literature Review (SLR), which is a literature review that finds, assesses and interprets all data about research problems to answer research questions. This literature review highlights the importance of applying technology in the cell biology learning process as a step to ensure the prevention of misconceptions or a reduction in misconceptions about the cell material being studied. By analyzing a number of relevant scientific articles, several technologies were identified that can be applied to cell learning, such as the application of Augmented Reality (AR) which can visualize microscopic cells as well as several software that can help the process of learning cell material. It is hoped that this research can provide new insights for teaching staff such as teachers to implement technology in cellular learning